Power and Interest Matrix Stakeholders of the Geothermal Development Project in Indonesia - Syaifullah, Adrian; Latief , Yusuf; Puja Dewi , Marmelia; Darma , Surya (Action Research Literate, 2024)
Indonesia has 23 GW of geothermal reserves and is ranked second with the largest geothermal installed capacity in the world. Currently, the electricity generated from geothermal energy is 2,418 MW, that only 10% of geothermal energy utilization in Indonesia. This is because geothermal projects are capital-intensive, complex, and sensitive to uncertainty and risk thus make the investment less viable. Based on the literature review, simplifying the geothermal development process can reduce project costs and accelerate project completion to make it more attractive One of them is the effectiveness of coordination between stakeholders related to geothermal development. This research aims to identify key stakeholders and map them based on the power and interest of each key stakeholder involved in geothermal development using the Stakeholder Analysis approach. The Delphi method is employed in this study, a group of experts contributes insights, revealing a clear pattern in identifying and mapping stakeholders in geothermal development in Indonesia. The final round result of expert validation led to the inclusion of 14 stakeholders in the key stakeholder category from 30 identified stakeholders initially. Among the 14 key stakeholders, an assessment based on power and interest was conducted. The results showed that 11 stakeholders were categorized as players, while 3 key stakeholders were classified as context setters.